Investing into North African Solar Power: A Legal Framework for Risk Management and Prospects for Arbitration - Gömmel, Robert (Springer, 2016)
This book investigates how a North African solar thermal power plant can be set up under the guidance of European investors (e.g. the Desertec Concept) as a Public Private Partnership (PPP). It outlines the importance of early awareness of contract-related risks, investment risks and dispute settlement, arguing that commercial and investment arbitration are the best tools for settling disputes regarding a large-scale solar thermal project. Furthermore, by comparing institutional and ad hoc arbitration, it shows that the former offers highly suitable support. The latest developments in the area of investment arbitration under EU law and the general acceptance of arbitration in Islamic countries are examined in particular. This book also demonstrates that a solar thermal power plant must meet certain requirements to be considered an investment. These requirements are examined in relation to Art. 25 of the International Centre for Settlement of Investment Disputes Convention (ICSID Convention) and respective case law. Overall, the book offers valuable guidelines for investors and host states on how to successfully implement large-scale solar thermal projects.